New synonym and descriptions of two new species of the spider genus Clubiona Latreille, 1804 from Thailand (Araneae, Clubionidae) - Dankittipakul, Pakawin; Tavano, Maria; Chotwong, Wimolwan; Singtripop, Tippawan (Zootaxa, 2012)
The female holotype of Clubiona distincta Thorell, 1887 from Myanmar is illustrated for the first time. It is considered ajunior synonym of C. filicata Pickard-Cambridge, 1874 originally described from India. Two new species belonging tothe genus Clubiona are described from Thailand. These taxa are C. digitata sp. nov., and C. aberrans sp. nov. The con-specific female of C. filifera Dankittipakul, 2008 is designated and described. Clubiona melanothele Thorell, 1895 and C. corrugata Bösenberg & Strand, 1906 are recorded from Thailand for the first time.